"Amazonizing" world cities through paintings: Indigenous cosmovisions encountering urban centers for the lost balance. (March 2022) - Mitsuishi, Katia Yoza
Currently, Peruvian Amazonian Indigenous artists are receiving unprecedented attention as they exhibit their paintings in galleries worldwide. In this context, I focus on three paintings of world cities as Havana, Miami, and Paris by Bora artist Brus Rubio (born 1984). Unfortunately, these paintings have not been analyzed from Indigenous studies and Amazonian Indigenous cosmologies. I argue that the paintings manifest Rubio's Amazonian resilience by offering a new imaginary of the urban space associated with Indigenous cosmologies, which facilitates the preservation of Indigenous lands, rights, and traditions for the globalized world. In this vision, the Western and the Indigenous worldview find harmony when the human and the non-human encounter and celebrate a balanced cohabitation as in Bora's narratives. This is his way of amazonizing the world or claiming his right to world citizenship and proposing a new understanding of globalization.